5.3k views
2 votes
Whucg expression is equivalent to (-4‐⁵)⁰?

User Touffy
by
5.7k points

1 Answer

5 votes

Solution

Step 1

State a law of indices that can be used to simplify the expression


(a^b)^c=(a)^(bc)

Step 2

Apply the law to solve the problem


\begin{gathered} \text{From the law, in relation to the question} \\ a\text{ = -4} \\ b\text{ = -5} \\ c\text{ = 0} \\ \text{Therefore, after substitution, we would have} \\ (-4^(-5)_{})^0 \\ (-4)^(-5*0) \\ (-4)^0 \end{gathered}

According to a law of indices, any number raised to the power of zero = 1

Therefore,


(-4)^{0\text{ }}=1

The right option, therefore, option A, 1

User Davidbilla
by
6.0k points